Peningkatan Kemampuan Bercerita Melalui Permainan Boneka Jari di Taman Kanak-Kanak - Evanofiana, Nina; Mahyuddin, Nenny; Izzati, Izzati (Penerbit Aksara Rentaka Siar (ARS), 2019)
The aim of this research is to improven the story telling ability of the children thought playing with the finger puppet in the kindergarten Rahmah Abadi Padang in order to be able to answer the more complex questions, to express the ideas or opinions of the story and to continue a part of the story. This research is the action class research by using quantitative method. Based on the data analysis, the result of the research in the improvement of the story telling ability thought playing finger puppet do not reach the criteria of the minimal exhaustiveness as determined yet. And this research is continued to the second cycles. On the second cycles the ability of the story telling increases the criteria of the minimal exhautiveness. This result describes that the story telling ability of the children is improved.